Electoral Fairness and the Law of Democracy: A Structural Rights Approach to Judicial Review - Dawood, Yasmin (University of Toronto Law Journal, 2012)
Partisan self-dealing in the design of election laws is a central challenge for democratic governance. This article develops a new conceptual framework, which I call a structural rights approach, that would enable the Supreme Court of Canada to respond effectively to this problem. A structural rights approach uses the language and logic of individual rights to regulate the structure of democratic institutions. In particular, I argue that courts should design democratic rights to remedy the structural deficiencies of the political system. To this end, I claim that the Supreme Court should interpret the right to vote as encompassing a new democratic right – the right to a fair and legitimate democratic process. In addition, I argue that the right to a fair and legitimate democratic process is best understood as a ‘structural right.’ I define ‘structural rights’ as individual rights that take into account the broader institutional framework within which rights are defined, held, and exercised. This article focuses on two cases studies – electoral redistricting and campaign finance – to show how the Court could use the right to a fair and legitimate democratic process to remedy the problem of partisan self-dealing. In addition, this article canvasses a wide array of structural approaches in the Canadian and American law of democracy literatures, and it locates the structural rights approach within this body of scholarship. The article also considers the structural rights approach with reference to theories of dialogue and deference. The structural rights approach not only provides a new paradigm for the Supreme Court’s oversight of the democratic process; it also offers an alternative way to conceptualize democratic rights.